SIMPLE PAST TENSE AND CONJUNCTION ERRORS IN WRITING RECOUNT TEXT - Daniel Buhis; Supadi Supadi (Universitas Indraprasta PGRI, 2019)
Abstract. This study aims to present the number and percentage of errors in using simple past tense and conjunction in writing recount text. The method used in this research is the descriptive qualitative method. This study's objects were 35 students of 12th (12th) grade 1 (one) of Link and Match Vocational School. This study's results are 179 findings (82%) errors in using simple past tense and 39 findings (18%) errors in using a conjunction. Keywords: error analysis; simple past tense; conjunction; recount text